1987
DOI: 10.1111/j.1365-2133.1987.tb05900.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of leukotriene B4-induced intraepidermal accumulation of polymorphonuclear leukocytes by methotrexate in psoriasis

Abstract: The leukotriene B4 (LTB4)-induced intraepidermal accumulation of polymorphonuclear leukocytes (PMN) was quantified, using an elastase assay, in psoriatic patients receiving methotrexate and in untreated psoriatic patients. Methotrexate in therapeutic dosages inhibited PMN infiltration in six patients who had improved considerably on treatment with the drug, a gradual increase being seen during the days on which no methotrexate was taken. Two patients were in relapse, despite methotrexate treatment, and both fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In addition, MTX decreases the neutrophil and monocyte chemotaxis, 17 and inhibits the leukotriene B4‐induced penetration of neutrophils 18 . Via interference with the vitamin D receptor, calcipotriol stimulates cellular differentiation, inhibits proliferation and plays an important part in immune modulation 19–21 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, MTX decreases the neutrophil and monocyte chemotaxis, 17 and inhibits the leukotriene B4‐induced penetration of neutrophils 18 . Via interference with the vitamin D receptor, calcipotriol stimulates cellular differentiation, inhibits proliferation and plays an important part in immune modulation 19–21 …”
Section: Discussionmentioning
confidence: 99%
“…LTB 4 is a highly specific leucocyte chemoattractant that is naturally present in lesional psoriatic skin. Epicutaneous application of LTB 4 induces artificial intra‐epidermal PMN accumulation with well‐established time and phase intervals . However, to the best of our knowledge, no real‐time in vivo studies have been performed so far that evaluate the dynamics of leucocyte accumulation in psoriasis or any inflammatory skin disease.…”
Section: Introductionmentioning
confidence: 99%
“…However methotrexate had an inhibitory effect on two functions of interleukin 1 in vitro. Several other studies suggest that neutrophil chemotaxis is depressed in the presence of methotrexate, indicating a direct or indirect effect of methotrexate on neutrophils with positive consequences on psoriatic lesions (39)(40)(41). Johnson et al (42) demonstrated in an adjuvant arthritis rat model that methotrexate, indomethacin and prednisolone are efficient antiinflammatory drugs, but only methotrexate had the ability to prevent systemic activation and local accumulation of inflammatory cells, whereas indomethacin and prednisolone suppressed only the ongoing local inflammatory process.…”
Section: Discussionmentioning
confidence: 96%